Replacing critical point drying with hexamethyldisilazane drying enhances the ultrastructural preservation of cell surface projections in the parasite Trichomonas vaginalis for scanning electron microscopy - Tuanne dos Santos Melo; Abigail Miranda-Magalhães; Regina Celia Bressan Queiroz de Figueiredo; Antonio Pereira-Neves (PLoS ONE, 2025)
The cell surface of Trichomonas vaginalis, causative agent of human trichomoniasis, plays a pivotal role in parasite adhesion, motility, and intercellular communication. Scanning electron microscopy (SEM) is widely used to explore the surface projections involved in these processes; however, standard sample preparation via critical point drying (CPD) often damages delicate membrane projections. Here, we optimized a hexamethyldisilazane (HMDS) drying protocol as a reliable alternative to CPD for ultrastructural analysis of T. vaginalis using SEM. Both drying methods were compared in terms of image quality and artifact formation. HMDS drying significantly improved the preservation of fragile projections, such as filopodia-, cytoneme-, and lamellipodia-like structures, compared to CPD. Our results show that susceptibility to CPD-induced artifacts may vary among highly adherent T. vaginalis strains, highlighting the need for caution in SEM interpretation. In a strain previously CPD-characterized by exhibiting a low number of cytonemes, quantitative analyses revealed a marked increase in the number of parasites with filopodia and cytonemes upon HMDS, accompanied by a reduction in drying-associated artifacts. In contrast, other strains exhibited similar quantitative results for both methods, though HMDS demonstrated a slight qualitative enhancement. HMDS drying also enabled the identification of novel ultrastructural features of T. vaginalis, including (a) long (>20 µm) cytonemes forming network-like connections between parasites and host cells, and (b) thin posterior and axostylar cytoneme-like structures that seems involved in host cell adhesion. Moreover, HMDS provided better morphological preservation of amoeboid forms and enhanced visualization of parasite–host interactions, revealing membranous networks not previously observed with CPD. Altogether, this study demonstrates the importance of the drying methods for sample preparation and expands the approaches for parasite imaging, revealing HMDS as a valuable option that could provide new ultrastructural insights into the surface morphology and intercellular communication mechanisms of T. vaginalis.